2014
DOI: 10.1007/s11434-014-0438-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic characteristics and its environmental implications of core YSJD-86GC sediments from the southern South China Sea

Abstract: Sediments of core YSJD-86GC (referred to as 86GC) collected from the southern South China Sea were selected for environmental magnetic studies. Combined with the published chronological framework, sediment magnetic properties were revealed for the study area since the MIS3 stage. The rock magnetic results indicate that low-coercivity magnetite is the main magnetic mineral within the sediments. Also, a certain amounts of hematite are present. The King plot and Day plot, which reflect the magnetic particle size,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…As the previous published research for the core PC24 (Ouyang et al, 2014a) suggested that both detrital (mainly pseudo single domain, PSD) and biogenic (mainly single domain, SD) magnetite were coexisted within core PC24 sediments. κ-T curves, hysteresis loops, IRM acquisition and backfield demagnetization curves, gradient acquisition plot of IRM acquisition curves from CLG analysis are illustrated at Figure 3 for representative samples.…”
Section: Magnetic Mineralogysupporting
confidence: 64%
See 3 more Smart Citations
“…As the previous published research for the core PC24 (Ouyang et al, 2014a) suggested that both detrital (mainly pseudo single domain, PSD) and biogenic (mainly single domain, SD) magnetite were coexisted within core PC24 sediments. κ-T curves, hysteresis loops, IRM acquisition and backfield demagnetization curves, gradient acquisition plot of IRM acquisition curves from CLG analysis are illustrated at Figure 3 for representative samples.…”
Section: Magnetic Mineralogysupporting
confidence: 64%
“…This correlation implies that total content of all magnetic particles is affected by a common factor. Total concentration of magnetic minerals within marine sediments was proved to be related to variation of temperature despite that sediment magnetic response to climate change differed from different regions within the SCS (Hou et al, 1996;Tang et al, 2003;Zhang et al, 2010;Ouyang et al, 2014a). Variation of χ lf , χ ARM and SIRM for the studied core PC24 was coincident with variation of χ lf for a previous reported core DSH-1C from the northern SCS before 6 cal.…”
Section: Sensitive Magnetic Parameters To Climatic Variationsupporting
confidence: 57%
See 2 more Smart Citations
“…Magnetic measurements provide a means of characterizing the mineralogy, concentration, and grain size of magnetic minerals contained in sediments in a rapid, economical and non-destructive way (Thompson and Oldfield, 1986). Therefore, the environmental magnetic method has been widely applied to characterize sediments and extract information regarding sediment provenance (Bloemendal et al, 1992;Jenkins et al, 2002;Liu et al, 2003;Booth et al, 2005;Wang et al, 2009;Ouyang et al, 2014), sedimentary dynamics (Rosenbaum et al, 1996;Yamazaki and Ioka, 1997;Watkins et al, 2007;) and post-depositional diagenesis (Demory et al, 2005;Karlin and Levi., 1983;Liu et al, 2004;Rowan et al, 2009;Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%